slamic Science: Theological Doctrine of Science Learning in Islamic Universities - Priatna, Tedi (International Journal of Psychosocial Rehabilitation, 2020)
this paper is intended to reveal the concept of Islamic science used in science learning in Islamic universities. The method used is phenomenology type of qualitative research. The data are analyzed philosophically, historically, and pedagogically. The results of this research show that Islamic science is a theological doctrine which sourced not only from the holy Quran but also from the scientific traditions of Moslems in the middle age. It also concerns with the social, politic, and cultural characteristics of Islamic education institution, specifically Islamic universities.